Usage Pattern of Social Media among Higher Secondary School Students of Haryana - Dhanwal, Sanyogita; Kundu, Poonam; Malik, Joginder Singh; Arun, Dangi Pooja; Kumari, Neelam (Indian Journal of Extension Education, 2022)
Social media is most modernistic form of media and acquire many features and characteristics. It has many facilities like as texting, communicating, images sharing, audio and video sharing, fast publishing, gaming, blogging, linking with all over world, direct connecting. Social media provides an opportunity for students to improve social networking and learning processes, which promotes knowledge in society. The study was conducted in year 2017-18 between rural and urban areas of Hisar district of Haryana. Thus total of 160 students were selected randomly. Results highlighted that the students keep themselves updated with latest know and how through newspaper (30.00%), television (83.70%), mobile phones (62.50%), and mobile with internet connections (43.70%). Majority of the students were aware and utilizing social media such as Facebook (90.00%), WhatsApp (95.00%), YouTube (75.00%), Messenger (47.50%) and Wikipedia (30.00%) respectively. The social media use was positively correlated with age, sex and stream of study and negatively associated with the academic performances of the students.
Keywords: Social media; Internet; Mobile phones; Communication; Facebook; WhatsApp